PERAN KOMUNIKASI INTERPERSONAL KONSELOR DALAM PENANGANAN PEREMPUAN KORBAN KEKERASAN (Studi Di Pusat Pelayanan Terpadu Provinsi Jawa Timur) - Syaifudin, Abu Bakar; Sumarah, Noorshanti; Rusmana, Dewi Andika (representamen, 2019)
Many woman have become voilance of victims. Some not receive an affection and protected,even from the closest person of her life. East java have become second rank with the highestlevel of violance against woman in Indonesia. Some of effort in preventing of woman fromvoilance is starting from family. Therefore, this study is aimed for the role of interpersonalcommunication that is conducted by the counselor of intregrated service centre of east java.By using Theory of five general quality references in interpersonal communication fromDevito, which is empathy, openness, positiveness, support and equality, The research wasconducted by using In depth Interview and observation to see directly how the role ofinterpersonal communication by the counselor of intergrated service centre of east java withthe woman a victims of violance. The result showed that the communication betweencounselor of the integrated service centre and woman victims of violance are doing most ofempathy, positiveness , openness, support, and equality.Keywords: Role, Interpersonal Communication, Woman, Violance.